European integration and the spatial dynamics of manufacturing employment change - Konstantinos Melachroinos (European Regional Science Association (ERSA), 2002)
This paper examines the dynamics of manufacturing employment change in 13 EU countries between the years 1978 and 1996 mainly through the utilisation of shift-share techniques. Despite the momentum that European integration gained over this period the key finding here is that the geography of manufacturing employment has remained almost intact. Processes operating at European scale appear to have the largest impact on labour outcomes in each member state, while there is little deviation from the widespread declining trends. Spatial stability is reinforced even further through the remarkable homogeneity of national industrial structures. In addition, the modest increase in the industrial specialisation of the participating economies and the moderate localisation tendencies of a few traditional sub-sectors pose little if any threat to the stability of the present map of manufacturing distribution. This evidence suggests that, contrary to some political rhetoric, the integration process has not, at least so far, adversely affected the relative competitiveness of manufacturing in either peripheral or core countries. Key words: Employment change, European integration, industrial specialisation, manufacturing, sectoral dispersion, shift-share.
Keywords: 330